CLINICAL AND ANAMNESTIC CHARACTERISTICS AND FEATURES OF PREGNANCY AND DELIVERY IN PATIENTS WITH COMPLICATED MONOCHORIONIC MULTIPLE PREGNANCY - Markova, Tatyana Vladimirovna; Shumakov, Sergey Yurievich; Kosovtsova, Natalya Vladimirovna; Kolomiets , Elizaveta Vladimirovna (Mother and Baby in Kuzbass, 2026)
Monochorionic multiple pregnancy is characterized by a high risk of specific complications associated with the presence of vascular anastomoses in the placenta. The key complications are twin-to-twin transfusion syndrome (TTTS) and selective fetal growth restriction (sFGR), which require timely diagnosis and treatment.Aim – to study the clinical, obstetric-gynecological, laboratory and ultrasound features of monochorionic diamniotic twin pregnancy complicated by TTTS and sFGR, and to assess their impact on perinatal outcomes and pregnancy management strategies.Materials and methods. A prospective study was conducted involving 178 patients with monochorionic diamniotic twins in the first trimester (2018-2023). Ultrasound scanning with marker assessment, Doppler imaging, serum marker analysis, placental pathomorphological examination, and statistical processing were performed.Results. The rate of threatened miscarriage in the first trimester was 41.1% in TTTS and 48.0% in sFGR; cervical insufficiency was 35.3% in TTTS. Antenatal fetal death was recorded in 17.6% (TTTS) and 26.9% (sFGR). Crown-rump length discordance >10% was associated with sFGR, while nuchal translucency discordance >20% was associated with TTTS. In sFGR, placental vascular network depletion and lobar asymmetry were revealed. Neonatal mortality was 10.8% in TTTS and 7.5% in sFGR.Conclusion. Prognostically significant markers are biometric discordance and abnormal ductus venosus blood flow. Complicated forms are characterized by a high rate of preterm birth, emergency cesarean section, neonatal morbidity and mortality, which requires early detection and specialized care.
Keywords: monochorionic twins; twin-to-twin transfusion syndrome; selective fetal growth restriction; ultrasound markers; Doppler imaging; placental anastomoses; perinatal outcomes; preterm birth